Evaluating the role of administrative development in improving institutional performance, an exploratory study in the Iraqi Ministry of Finance 2024 (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to identify the relationship between development and institutional performance, as well as strategic goals and raising the effectiveness of employees in ministries. The problem of the study was the weakness of the mechanisms used in institutional performance in the ministry, as there is still reliance on traditional standards that are no longer sufficient to judge its performance in an accurate and comprehensive manner in light of the changes. This is accompanied by weak interest in developing and improving institutional performance standards in the Ministry and applying modern techniques in measuring performance. The descriptive and descriptive analytical methodologies were followed. The study population was the Ministry of Finance and the sample was the Administrative Department. The research concluded that the Ministry’s administration supports the administrative development of employees through the Deanship of Development and Quality supervising the Activities in departments and sections.